SPIRITUALITAS DAN TINGKAT KECEMASAN PERAWAT DALAM MERAWAT PASIEN HEMODIALISIS DENGAN COVID-19 - Santi Herlina (Indonesian Journal of Health Development, 2023)
The anxiety of health workers, especially nurses during a pandemic, is an important problem, especially for nurses, whose interaction intensity with patients is quite high. One of them is in the hemodialysis unit, where the average patient is an outpatient with more interaction between parties outside the hospital, so the risk of carrying the virus is quite high which will be at risk of transmitting it to the hemodialysis nurse. The average hemodialysis patient is an outpatient so that contact with outsiders is quite high which will be at risk of carrying the virus. The aim of this study analyzing spirituality with the anxiety level of nurses when caring for hemodialysis patients infected with Covid-19. The design in this study was cross sectional which was carried out on 19 hemodialysis nurses who treated Covid-19 patients with a total sampling technique. Data was collected using two instruments, namely the Spiritual Well-Being Scale (TSWBS) and the Beck Anxiety Inventory (BAI). The results of the analysis show that there is no relationship between spirituality and the anxiety level of nurses when caring for hemodialysis patients who are infected with Covid-19 with a p value of 0.340. Suggestions for further research increase the number of samples and analyze other factors that influence nurse anxiety such as family support.